THE CONCEPT OF PARTNERSHIP AND ITS RELATIONSHIP BETWEEN FAMILY AND EDUCATION’S IMPORTANCE - Kamolova , Ozodakhan Muzaffar kizi (Innovative Development in Educational Activities, 2023)
In this article, the concept of cooperation and the teacher’s use of cooperation technology in the process of working with the family, the formation of the active pedagogical position of the parents and the content of working with the family in the school education system are discussed.